IIIB-IV Degree Perineal Rupture Repair Using Overlapping and End-to-End Techniques with Pudendal Block Anesthesia - Nuring Pangastuti; Junizaf Junizaf; Ibnu Pranoto; Budi I Santoso; Tyas Priyatini (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To compare the incidence of persistent sonographic anal sphincter defect, fecal urgency, anal and fecal incontinence after IIIb- IV degree perineal rupture repair using overlapping and end-to-end technique. Method: An open clinical trial with randomization was carried out in July 2010-April 2012. The population consisted of the patients who underwent vaginal delivery in Dr. Sardjito Central General Hospital, Sleman District General Hospital, as well as Tegalrejo, Jetis and Mergangsan Community Health Centers who did no have complaints of fecal urgency, anal incontinence, and/or fecal incontinence, and suffered IIIb-IV degree perineal rupture repaired within less than 24 hours of rupture. The exclusion criteria included conditions in which patients could not undergo repair at the moment (shock, uncooperative patient). Fourty-eight research samples were divided into 2 groups, 24 samples for each of the treatment group (overlapping repair) and the control group (end-to-end repair). Local anesthesia was performed in a pudendal-block manner. Result: Success of the repair was assessed based on the presence of persistent sonographic anal sphincter defects in the 6-week evaluation after repair. Successful repair was higher in the overlapping group than that of the end-to-end group (94.74% vs 81.25%, p=0.31). Clinically and based on the Fecal Continence Scoring Scale (FCSS), evaluation at weeks II and VI indicated successful repair in both groups. Conclusion: There was no difference in the incidence of persistent sonographic anal sphincter defects, fecal urgency, anal incontinence, and fecal incontinence, after IIIb-IV degree perineal rupture repair using overlapping technique in comparison with end-to-end technique. Keywords: end-to-end technique, III-IV degree perineal rupture, obstetric perineal rupture, overlapping technique